2003
DOI: 10.1074/jbc.m302488200
|View full text |Cite
|
Sign up to set email alerts
|

The Association of the Human PM/Scl-75 Autoantigen with the Exosome Is Dependent on a Newly Identified N Terminus

Abstract: The exosome is a complex of 3 3 5 exoribonucleases that functions in a variety of cellular processes, all concerning the processing or degradation of RNA. Paradoxically, the previously described cDNA for the human autoantigenic exosome subunit PM/Scl-75 (Alderuccio, F., Chan, E. K., and Tan, E. M. (1991) J. Exp. Med. 173, 941-952) encodes a polypeptide that failed to interact with the exosome complex. Here, we describe the cloning of a more complete cDNA for PM/Scl-75 encoding 84 additional amino acids at its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…The distribution of the exosome complex has been confirmed in these cellular locations, with the highest concentration reported in the nucleoli (Raijmakers et al, 2003(Raijmakers et al, , 2004. This is not the case with the CER7 protein in Arabidopsis.…”
Section: Discussionsupporting
confidence: 53%
“…The distribution of the exosome complex has been confirmed in these cellular locations, with the highest concentration reported in the nucleoli (Raijmakers et al, 2003(Raijmakers et al, , 2004. This is not the case with the CER7 protein in Arabidopsis.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have shown that human exosome subunits are localized both in the nucleus and particularly enriched in the nucleolus and in the cytoplasm (37,38). However, it was not reported that cytoplasmic exosome subunits are localized to discrete granules.…”
Section: Amd Requires Function Of Parn-mentioning
confidence: 92%
“…However, it was not reported that cytoplasmic exosome subunits are localized to discrete granules. Because the nuclear/nucleolar staining of exosome subunits is usually stronger than that of cytoplasmic signals (37,38), the appearance of cytoplasmic exosome granules might have been overlooked. Our finding of human exosome subunits concentrated in cytoplasmic granules is consistent with a recent study suggesting that several Drosophila exosome subunits are enriched in cytoplasmic foci (40).…”
Section: Amd Requires Function Of Parn-mentioning
confidence: 99%
“…The full-length PM-Scl-75 open reading frame was amplified from PM-Scl-75c construct (Raijmakers et al 2003) using the primers 59-CCGAGCCTGCAGATGAAGGAAAC GCCACTCTCA and 59-GACCGGTACCTTAATTGGCAGCTCTC CTCTT. Select domains of the protein were amplified from the plasmid as follows: Primers to amplify the C-terminal amino acids 351-439 were 59-AATAAACTGCAGAGACTCTGAGAAGGAAG ATGATGAA and 59-AATGCTTCGAATTCCCATATGGTAC; primers to amplify the C-terminal amino acids 285-439 were 59-AATAAACTGCAGAGAGTCTATAGCAAATCAAAGGATC and 59-AAGCTTCGAATTCCCATATGGTAC.…”
Section: Methodsmentioning
confidence: 99%